Early intervention for preventing posttraumatic stress disorder: an Internet-based virtual reality treatment - Freedman, Sara A. (Eur J Psychotraumatol, 2015)
BACKGROUND: Posttraumatic stress disorder (PTSD) develops in approximately 20% of people exposed to a traumatic event, and studies have shown that cognitive-behavioral therapy (CBT) is effective as a treatment for chronic PTSD. It has also been shown to prevent PTSD when delivered early after a traumatic event. However, studies have shown that uptake of early treatment is generally low, and therefore, the need to provide interventions through other mediums has been identified. The use of technology may overcome barriers to treatment. OBJECTIVE: This paper describes a randomized controlled trial that will examine an early CBT intervention for PTSD. The treatment incorporates virtual reality (VR) as a method for delivering exposure-based elements of the treatment. The intervention is Internet based, such that the therapist and patient will “meet” in a secure online site. This site will also include multi-media components of the treatment (such as videos, audios, VR) that can be accessed by the patient between sessions. METHOD: Two hundred patients arriving to a Level 1 emergency department following a motor vehicle accident will be randomly assigned to either treatment or control groups. Inclusion criteria are age 18–65, PTSD symptoms 2 weeks posttrauma related to current trauma, no suicidality, no psychosis. Patients will be assessed by telephone by a team blind to the study group, on four occasions: before and after treatment, and 6 and 12 months posttreatment. The primary outcome is PTSD symptoms at follow up. Secondary outcomes include depression and cost effectiveness. Analyses will be on an intention-to-treat basis. DISCUSSION: The results will provide more insight into the effects of preventive interventions, in general, and Internet-based early interventions, in particular, on PTSD, in an injured population, during the acute phase after trauma. We will discuss possible strengths and limitations.